Analisis Tegangan Untuk Setiap Kapasitas Belt Conveyor C4 PLTU Indramayu 3 X 330 Mw - Ammar Asof; Nurmiati Pasra; Ulil Absor (JURNAL POWERPLANT, 2014)
Belt conveyor is a device used to transfer coal combustion chamber (furnice) in Steam Power (power plant). In the Indramayu power plant conveyor conditions in the field often occurs over tracking the conveyor belt and the belt results in the termination of coal burning. A voltage that is too large will cause the working of the belt conveyor to be heavy so that it can lead to broken shaft and idler pulley. While the voltage is too small to make the cause of the conveyor belt out of the track resulting in slippage into the pulley. The voltage on the conveyor belt must be known with certainty to prevent failed operations on the conveyor. In this case penlis will analyze the voltage for each operating capacity of belt conveyor C4 using the standard CEMA (Conveyor Equipment Manufacturers Association) 6th Edition, 2002. So with the proper voltage, the operation of conveyor C4 can walk normally.